2009
DOI: 10.1016/j.biopsych.2008.11.004
|View full text |Cite
|
Sign up to set email alerts
|

What is an “Adverse” Environment? Interactions of Rearing Experiences and MAOA Genotype in Rhesus Monkeys

Abstract: Background-Studies have been inconsistent in demonstrating that early adversity and specific genotype can be joint risk factors for poor behavioral outcomes. Using a rhesus monkey model, we examined how social context and different forms of early adversity influence whether a specific genotype (polymorphism in the promoter region of monoamine oxidase A) affects display of aggressive, fearful, and anxious behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 20 publications
7
57
0
Order By: Relevance
“…In rhesus monkeys, the MAOA polymorphism is associated with early rearing environment-dependent differences in aggressive behavior (Newman et al, 2005). This result was replicated and extended in a large study (n ¼ 473) of the interactive effects of the MAOA genotype on multiple aspects of socioaffective behavior expressed under challenge (Karere et al, 2009). In an elegant demonstration of the interplay between specific genetic variation and ''broader contextual features'' of the social environment, Karere et al showed that both genotype and the size of the social group in which mother-reared monkeys were raised contributed to aggression and anxiety.…”
Section: Other Genesmentioning
confidence: 65%
See 2 more Smart Citations
“…In rhesus monkeys, the MAOA polymorphism is associated with early rearing environment-dependent differences in aggressive behavior (Newman et al, 2005). This result was replicated and extended in a large study (n ¼ 473) of the interactive effects of the MAOA genotype on multiple aspects of socioaffective behavior expressed under challenge (Karere et al, 2009). In an elegant demonstration of the interplay between specific genetic variation and ''broader contextual features'' of the social environment, Karere et al showed that both genotype and the size of the social group in which mother-reared monkeys were raised contributed to aggression and anxiety.…”
Section: Other Genesmentioning
confidence: 65%
“…Together they suggest many paths for subsequent study aimed at uncovering the mechanisms by which monkeys' early environment and specific genes interact to produce differential associations on behavior and physiology, as well as their underlying neural substrates. For example, evidence that the interaction between genotype and the rearing environment is manifest within the first months of life after exposure to the environmental manipulation (Champoux et al, 2002;Karere et al, 2009;Kraemer et al, 2008), may be among the most significant clues these results hold for future mechanistic studies. The emergence of this effect so early in life helps to narrow, and thus facilitate, definition of the set of specific factors by which the environment induces genotype-dependent effects on neurobehavioral development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on rhesus monkeys mirrored these observations. Rhesus monkeys that were reared under adverse social conditions (small social groups versus large interactive groups) were more aggressive, especially when they carried the MAOA allele corresponding to low levels of enzyme activity (59).…”
Section: Implication Of Bioaminesmentioning
confidence: 99%
“…Studies in humans, mice and monkeys revealed a relationship between genetic variants of the neurotransmitter monoamine oxidase (MAOA) and the level of individual aggression (Brunner et al, 1993;Popova et al, 2001;Karere et al, 2009), whereas Lühken et al (2010 found no significant relationships between MAOA gene polymorphism and behavioural traits in beef breeds of cattle. Moreover, Glenske et al (2011) reported a low relationship between the dopamine receptor D4 (DRD4) gene located near QTL for behavioural traits on chromosome 29, and temperament of German Angus cattle.…”
Section: Candidate Genes For Behavioural Traits In Cattlementioning
confidence: 99%